Formação inicial na educação infantil : potencialidades no estágio e na docência - Defaveri, Bruna Battistel (My University, 2024)
The following dissertation aims to investigate which potentialities in the upbringing of teachers are interlaced to the supervised internship, experienced in the context of primary education, with students from the Pedagogy Licensing course, in a community university, in order to place the supervised internship in the Primmary Education, identifying the potentialities and challenges experienced by the students in the upbringing of teachers, analysing which knowledge is mobilized, that contributes for the internship to happen and its tangles between theory and practice. The theoretical framework in this study is based mainly in ?Nóvoa (1992; 2009; 2019; 2015; 2022), Pimenta (2005; 2021), Barbosa (2006; 2013; 2018; 2022), Tardif (2015) and Freire (2021)", authors that contribute for reflections about the teaching in the primmary education, supervised internship and beginning of teachers's upbringing, among others. This research, of a qualitative approach, based itself, mainly, in the study case with the benchmarks of "Yin (2005), Morés (2012), and Lüdke and André (2013)". The study case gazed the document analysis of the Pedagogical Political Project in the course of a community university and the internship project and the final article of three students from the Pedagogy Licensing course. Therefore, for the data analysis, the Textual Discourse Analysis (TDA) was used, grounded in "Moraes and Galiazzi (2020)". Starting from this analysis, two general categories emerged, the knowing: "teaching know-how and teaching upbringing paths" and "experienced upbring potential in the primmary education", and a meta-text: "The potential of continuing teacher upbring". The results of this research reverberated in some potentialities that the supervised internship provides for the training of teachers in the pedagogy degree course, such as: (1) Possibility of experiencing the profession; (2) Self-recognition and awareness of teaching identity; (3) Possibility of choosing and recognizing continuing education; (4) Recognition of the internship while researching. However, some challenges were also encountered, such as (1) some gaps between theory and practice; (2) Very broad training, without theoretical pedagogical depth; (3) Learning to recognize teaching in Early hildhood Education; (4) The relevance of undergraduate training being taught by pedagogues. Thus, the supervised internship was perceived as a training potential that greatly contributes to the training and appreciation of teachers at a time when teachers, together with their peers, can learn and experience their profession, contributing to improving the quality of education. [resumo fornecido pelo autor]
Esta dissertação objetivou investigar quais as potencialidades na formação de professores estão entrelaçadas ao estágio supervisionado, vivenciado no contexto da Educação Infantil, com estudantes do curso de Licenciatura em Pedagogia, em uma universidade comunitária, a fim de contextualizar o estágio supervisionado na Educação Infantil, identificando as potencialidades e desafios vivenciados pelas estudantes na formação de professores, analisando quais os saberes são mobilizados, que contribuíram para a realização do estágio e seus entrelaçamentos entre teoria e prática. O aporte teórico deste estudo fundamenta-se principalmente em Nóvoa (1992; 2009; 2019; 2015; 2022), Pimenta (2005; 2021), Barbosa (2006; 2013; 2018; 2022), Tardif (2015) e Freire (2021), autores que contribuem para as reflexões sobre a docência na educação infantil, estágio supervisionado e formação inicial de professores, entre outros. Esta pesquisa, de abordagem qualitativa, baseou-se, especialmente, no estudo de caso com os referenciais de Yin (2005), Morés (2012), e Lüdke e André (2013). O estudo de caso contemplou a análise documental do Projeto Político Pedagógico do curso de uma universidade comunitária e o projeto de estágio e o artigo final de três estudantes do curso de Licenciatura em Pedagogia. Por conseguinte, para a análise dos dados, utilizamos a Análise Textual Discursiva (ATD), embasada em Moraes e Galiazzi (2020). A partir dessa análise, emergiram duas categorias gerais, a saber: "saberes docentes e trajetórias da formação docente" e "o potencial formativo da vivência na educação infantil"; e um metatexto: "O potencial da formação continuada de professores". Os resultados desta pesquisa reverberaram em algumasc potencialidades que o estágio supervisionado proporciona para a formação de professores no curso de licenciatura em pedagogia como: (1) Possibilidade de vivenciar a profissão; (2) Reconhecimento de si e tomada de consciência identitária da docência; (3) Possibilidade de escolha e de conhecimento da formação continuada; (4) Reconhecimento do estágio enquanto pesquisa. No entanto, também foram encontrados alguns desafios, como (1) alguns distanciamentos entre teoria e prática; (2) Formação muito ampla, sem aprofundamentos teóricos pedagógicos; (3) Aprender a reconhecer a docência na Educação Infantil; (4) A relevância das formações em licenciatura serem ministradas por pedagogos(as). Assim, o estágio supervisionado foi percebido como potencial formativo que muito contribui com a formação e com a valorização dos professores em um momento em que os professores, junto a seus pares, podem aprender e vivenciar sua profissão, contribuindo com a melhora da qualidade da educação. [resumo fornecido pelo autor]
Keywords: Programas de estágio; Educação infantil; Professores - Formação; Professores de educação infantil - Formação; Internship programs; Education of children; Teachers, Training of; Early childhood education teachers - Training of